An initial study of the diagnostic utility of the emotional and behavioural screener in Lithuania. Issue 1 (1st January 2018) - Sointu, Erkko; Lambert, Matthew C.; Nordness, Philip D.; Geležinienė, Renata; Epstein, Michael H.
Abstract: In schools, screening is an effective method to identify students at-risk for emotional and behavioural disorders. Several intervention programmes such as Positive Behaviour Interventions and Supports, Response to Intervention, and Multi-tiered Systems of Supports call for the use of psychometrically sound screening instruments. This study investigated diagnostic utility of a brief (10-item) screener, the Emotional and Behavioural Screener (EBS) with a sample 312 Lithuanian students. The Strengths and Difficulties Questionnaire was used as a reference point for the investigation. Diagnostic utility statistics (i.e. overall agreement, misleading negatives, sensitivity, specificity and area under the receiver operating characteristic curve) were used to evaluate the usefulness and validity of the EBS. The results indicate, that majority of the diagnostic utility statistics thresholds were met; however, some gender differences were found. In sum, the EBS appears to be an accurate screener discriminating students not at-risk and at-risk for emotional and behavioural problems. Study limitations, future research directions and implications are discussed.